Steam Technologies as A Tool in Teaching English - Irgasheva Umida Raimjanovna (Scientific Trends, 2025)
The article explains the STEAM (Science, Technology, Engineering, Arts and Mathematics) technologies as a tool in teaching English as a foreign language. It proves that educators can make learning more relevant, engaging, and effective by integrating science, technology, engineering, arts, and math into language instruction. Ways of integrating STEAM technologies into English lessons are shown here. The approaches to teaching English using STEAM technologies and the methodological support for the development of communicative, linguistic, sociolinguistic, pragmatic, speech and lexical competences with the help of STEAM technologies in teaching English are pointed out in the research.
Keywords: Integrate, project-based methodology, creative, problem-solving, engage, interactive, logical thinking, unique, encourage, challenge, collaboration.